Pointed Hopf algebras over some sporadic simple groups - Andruskiewitsch, Nicolas (2010)
Any finite-dimensional complex pointed Hopf algebra with group of group-likes isomorphic to a sporadic group, with the possible exception of the Fischer group Fi22, the Baby Monster B and the Monster M, is a group algebra.